THE ROLE OF ISLAMIC FINANCIAL LITERACY AND ISLAMIC FINANCIAL INCLUSION ON BUSINESS PERFORMANCE OF MUSLIM GEN Z AND MILLENNIAL ENTREPRENEURS IN INDONESIAN MSMEs. - Dita Herdian (PT. Samudra Solusi Profesional, 2025)
The rapid development of Islamic finance presents significant opportunities for strengthening the performance of micro, small, and medium enterprises (MSMEs), particularly those owned by Muslim entrepreneurs. However, limited Islamic financial literacy and low access to Sharia-compliant financial services remain critical challenges, especially among younger generations. This study aims to examine the role of Islamic financial literacy and Islamic financial inclusion in enhancing business performance among Muslim Gen Z and millennial entrepreneurs operating MSMEs in Indonesia. Using a quantitative research approach, primary data were collected through an online questionnaire distributed to Muslim MSME entrepreneurs who have operated their businesses for at least two years. A total of valid responses were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that Islamic financial literacy has a positive and significant effect on Islamic financial inclusion, indicating that higher levels of Sharia-based financial knowledge increase entrepreneurs’ access to and use of Islamic financial services. Furthermore, Islamic financial literacy is found to have a direct and significant impact on business performance, suggesting that financially literate Muslim entrepreneurs are better equipped to manage financial decisions, optimize resources, and sustain business growth. Islamic financial inclusion also demonstrates a positive and significant influence on business performance, highlighting the importance of access to Sharia-compliant financing and financial products in improving MSME outcomes. In addition, mediation analysis confirms that Islamic financial inclusion significantly mediates the relationship between Islamic financial literacy and business performance. These findings underscore the strategic importance of strengthening Islamic financial literacy and expanding Islamic financial inclusion to enhance the performance and sustainability of Muslim-owned MSMEs, particularly among Gen Z and millennial entrepreneurs. The study provides practical implications for policymakers, Islamic financial institutions, and entrepreneurship development programs in designing targeted interventions to support young Muslim entrepreneurs and foster an inclusive Islamic economic ecosystem.